2012
DOI: 10.1016/j.micromeso.2012.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of LEV-type zeolite into less dense CHA-type zeolite

Abstract: Hydrothermal conversion of LEV-type zeolite into CHA-type zeolite occurred in the absence of both an organic structure-directing agent and a seed crystal. The LEV-CHA transformation proceeds from a more dense zeolite (LEV) to a less dense one (CHA).When amorphous aluminosilicate hydrogels were used as starting materials, the CHA-type zeolite was not obtained under the present hydrothermal synthesis 2 conditions. From the fact that the LEV-CHA transformation proceeded at lower alkalinity conditions, it was sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 37 publications
(36 reference statements)
0
43
0
3
Order By: Relevance
“…As can be seen in Table 2, these zeolites have similar composite building units. Figure 5 shows the XRD patterns of the products obtained at various hydrothermal treatment times 42) . The findings clearly show that the starting LEV type zeolite decomposed into an amorphous phase, and then the pure CHA type zeolite crystallized after 1.5 h of hydrothermal treatment.…”
Section: Transformation Of Lev Into Chamentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in Table 2, these zeolites have similar composite building units. Figure 5 shows the XRD patterns of the products obtained at various hydrothermal treatment times 42) . The findings clearly show that the starting LEV type zeolite decomposed into an amorphous phase, and then the pure CHA type zeolite crystallized after 1.5 h of hydrothermal treatment.…”
Section: Transformation Of Lev Into Chamentioning
confidence: 99%
“…Catalytic performance for ethanol conversion to light olefins was evaluated. Figure 8 shows the relationship between the Si/Al ratio and initial ethylene and propylene yields at 0.5 h time-on-stream 42) . The ethylene and propylene yields were strongly dependent on the Si/Al ratio, and the maximum propylene yield of about 48 C-% was obtained at the Si/Al ratio of about 15.…”
Section: Catalyst For Ethanol To Olefin Reactionsmentioning
confidence: 99%
“…Hydrothermal conversion of a low density zeolite into a high-density zeolite is possible; for example, they transformed zeolite Y (FAU) transformed into SSZ-13 (CHA) 27) 33) . More recently, rapid crystallization of various zeolites was achieved from an FAU-type zeolite in the presence of a specific OSDA 34) 47) , including the successful transformation of the FAU phase into B E A 34) 36) , R U T 37), 38) , C H A 39) 41) , L E V 42) 44) , MTN 34), 45) , and OFF phases 46) . Synthesis of CHA-type zeolite from LEV-type zeolite was also reported 47) .…”
Section: Hydrothermal Conversion Using Fau-typementioning
confidence: 99%
“…More recently, rapid crystallization of various zeolites was achieved from an FAU-type zeolite in the presence of a specific OSDA 34) 47) , including the successful transformation of the FAU phase into B E A 34) 36) , R U T 37), 38) , C H A 39) 41) , L E V 42) 44) , MTN 34), 45) , and OFF phases 46) . Synthesis of CHA-type zeolite from LEV-type zeolite was also reported 47) . Locally ordered aluminosilicate species resulting from the decomposition and dissolution of FAU-type zeolites under hydrothermal conditions may be present in the synthetic media, and that assembling such aluminosilicate species with the aid of OSDAs leads to the observed increased rates of crystallization.…”
Section: Hydrothermal Conversion Using Fau-typementioning
confidence: 99%
“…[45] They also reported the transformation of a LEV-type zeolite into a CHA-type zeolite. [46] This work suggested that locally ordered aluminosilicate species resulting from the decomposition and dissolution of FAU-type zeolites under hydrothermal conditions are present in the synthetic media, and that assembling such aluminosilicate species with the aid of SDAs leads to the observed increased rates of crystallization.…”
Section: Introductionmentioning
confidence: 95%